(untitled) (Bangladesh Journal of Animal Science, 2012)
The present study was undertaken to collect the quality cumulus-oocyte-complexes (COCs) from ovaries of goat from slaughterhouse by aspiration to establish the suitable culture condition for in vitro maturation (IVM), in vitro fertilization (IVF) and in vitro culture (IVC). Follicular COCs were collected from follicles of 2-6 mm diameter, categorized by microscopic observation and cultured for 22 h in TCM-199 medium supplemented with 5% fetal calf serum (FCS) to determine the success rate of in vitro maturation in a condition of 5% CO2 in air at 38.5°C. The collected ovaries were classified as type-I (corpus luteum absent) and type-II (corpus luteum present). The average numbers of follicles aspirated per ovary were 3.15 and 2.57 in type-I and type-II, respectively. The collected COCs were classified into normal COCs (grade A and B) and abnormal COCs (grade C and D). The number of normal and abnormal COCs collected from two type of ovaries were significantly (P<0.01) differed. Average number of normal COCs per ovary obtained from type-I (1.30) was significantly (P<0.01) higher than that of type-II (0.68). Within the normal COCs significantly (P<0.01) higher maturation was obtained in grade A COCs (71.70%) than that of grade B (51.52%). The matured COCs were cultured for 5 h with fresh buck semen in Brackett and Oliphant (BO) medium and assumed that the COCs were fertilized successfully. In progress, IVC was practiced in TCM-199 supplemented with FCS and bovine serum albumen (BSA) at 38.5°C with 5% CO2 for 6-7 days. The rate of development to compact morula was found significantly (P<0.01) higher in grade A (25.64%) compared to grade B COCs (6.89%) and similar trend of blastocyst was found in grade A COCs (12.82%) than that of grade of B (3.45%). The results suggested that culture condition for IVM, IVF and IVC was found optimum and grade A COCs might be suitable for in vitro production (IVP) of goat embryos. DOI: http://dx.doi.org/10.3329/bjas.v37i1.9859 BJAS 2008; 37(1): 1-9